Ensino da primeira lei da termodinâmica por meio de simulações computacionais no contexto da metodologia da sala de aula invertida - Matiasso, Rosicler (2022)
This research is based on the need to contribute to the qualification of the teaching-learning process in Physics, through the use of strategies for teaching the 1st Law of Thermodynamics. Its general objective is to investigate the potential of using the inverted classroom methodology associated with computer simulations in the process of teaching Thermodynamics with high school students. Active methodologies, which in practice involve in-person and online teaching, arouse the interest and autonomy of the student for research and curiosity in the use of technological tools, which has become one of the forms of teaching, also referenced by authors as “hybrid education”. Hybrid teaching can be classified into teaching models, including flipped classroom teaching, or inverted classroom, a pedagogical model that inverts the traditional teaching of learning. Computer simulations allow the student to change initial values of variable parameters and thus observe how the physical phenomenon behaves in the face of changes. The educational product, based on the active inverted classroom methodology, was structured in three moments: pre-class, during class and after-class, in which it conceptualizes and characterizes Work, Heat, Internal Energy and the 1st law of Thermodynamics. Methodologically, the research proposed in this study is characterized as a qualitative approach, and in terms of its objectives as explanatory and in terms of technical procedures as participatory research. The proposed didactic product will be evaluated using the Delphi technique and, for this purpose, it will be submitted to the qualitative evaluation of eleven teachers from the Basic Education - with postgraduate training, who work (or acted) as teachers in classes of 2nd year high school students, in the discipline of Physics -, through an assessment protocol, produced specifically to analyze different aspects of the didactic product in question. Through this evaluation, by specialists who work in the classroom, following the steps of the Delphi method, it was possible to conclude that the general and specific objectives of the dissertation were fulfilled. And that the Educational Product provides students with a strategy of understanding, interpretation and graphic representation of concepts related to the First Law of Thermodynamics. Finally, it is noteworthy that this dissertation (in the qualification phase) is composed of an educational product in the form of a sequence of activities developed with the aim of providing didactic-methodological support to high school physics teachers and which will be available in <http://educapes.capes.gov.br/handle/capes/701629>.